2013 International Conference on Privacy and Security in Mobile Systems (PRISMS) 2013
DOI: 10.1109/prisms.2013.6927181
|View full text |Cite
|
Sign up to set email alerts
|

Security for smart mobile networks: The NEMESYS approach

Abstract: Abstract-The growing popularity of smart mobile devices such as smartphones and tablets has made them an attractive target for cyber-criminals, resulting in a rapidly growing and evolving mobile threat as attackers experiment with new business models by targeting mobile users. With the emergence of the first large-scale mobile botnets, the core network has also become vulnerable to distributed denial-of-service attacks such as the signaling attack. Furthermore, complementary access methods such as Wi-Fi and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Network worms were also considered, and CPN was used to reroute the users' traffic to avoid the infected nodes (Sakellari and Gelenbe [176], Sakellari, Hey, and Gelenbe [177]). Further research on network security can be found in (Gelenbe et al [87], Gorbil et al [151], Yu et al [185]). …”
Section: Autonomic Systems and Cognitive Packet Network (Cpns)mentioning
confidence: 99%
“…Network worms were also considered, and CPN was used to reroute the users' traffic to avoid the infected nodes (Sakellari and Gelenbe [176], Sakellari, Hey, and Gelenbe [177]). Further research on network security can be found in (Gelenbe et al [87], Gorbil et al [151], Yu et al [185]). …”
Section: Autonomic Systems and Cognitive Packet Network (Cpns)mentioning
confidence: 99%
“…The original purpose of the aforementioned firewall policies could have been prevention of undesired incoming connections and P2P data transfer between different mobile network users. As a result, they deny any and all P2P connectivity over cellular networks [21].…”
Section: Providing Unrestricted Ip Connectivitymentioning
confidence: 99%
“…The original purpose of the aforementioned firewall policies could have been prevention of undesired incoming connections and P2P data transfer between different mobile network users. As a result, they deny any and all P2P connectivity over cellular networks [21].For the purposes of our network-assisted D2D trial, we needed to circumvent the firewall by making the D2D server open direct communication paths for selected connections whenever necessary. In our case, implementing such functionality has been fairly straightforward, since the D2D server can reconfigure the firewall on a per-connection basis.…”
mentioning
confidence: 99%
“…And, a detection model is trained with the information gathered via the communication among components. A security framework has been deployed by an European project called NEMESYS for gathering and analyzing information about the nature of cyber-attacks targeting mobile devices and presented a model-based approach for detection of anomalies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%